2018
DOI: 10.3904/kjim.2015.385
|View full text |Cite
|
Sign up to set email alerts
|

Drug survival and the associated predictors in South Korean patients with rheumatoid arthritis receiving tacrolimus

Abstract: Background/AimsTo investigate the drug survival rate of tacrolimus (TAC) and analyze the potential predictors of this rate in patients with rheumatoid arthritis (RA) in routine care.Methods2018-01-16In this retrospective longitudinal study, we enrolled 102 RA patients treated with TAC from April 2009 to January 2014 at a tertiary center in South Korea. The causes of TAC discontinuation were classified as lack of efficacy (LOE), adverse events (AEs), and others. The drug survival rate was estimated using the Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Although persistence is a multifaceted measure that considers factors beyond treatment efficacy, including safety, tolerability and patient satisfaction or preferences, it is also often used as a surrogate for efficacy in the real world [ 26 28 ]. Using persistence as a broad marker of efficacy here, there were no differences between the 3 treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although persistence is a multifaceted measure that considers factors beyond treatment efficacy, including safety, tolerability and patient satisfaction or preferences, it is also often used as a surrogate for efficacy in the real world [ 26 28 ]. Using persistence as a broad marker of efficacy here, there were no differences between the 3 treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Kawai et al also have indicated that TAC is effective and relatively safe even in elderly RA patients who had an insufficient response to DMARDs [ 24 ]. High retention rates of TAC treatment were also reported in South Korean RA patients with a favorable efficacy and safety profile (69.1% of 4-year retention rates) [ 26 ]. In fact, relatively higher retention rates were observed in our cohort (69.7%) in ABT/TAC combination group.…”
Section: Discussionmentioning
confidence: 99%
“…Drug persistence can be interpreted as surrogate markers for long-term efficacy, safety, and tolerability and should be considered in real-world decision making [26][27][28], because lifelong treatment with DMARDs is required for patients with RA [2,3]. Thus, identifying associated factors for and promoting drug persistence are crucial for optimal care of RA patients.…”
Section: Discussionmentioning
confidence: 99%